Psychological Analysis of the Character of Mrs. Prani in the Film Budi Pekerti by Wregas Bhanuteja - Puspitasari, Syafira Aulia; Rohmah, Nur (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study aims to examine the psychological and emotional state of the character Prani, a mother in the film Budi Pekerti. This study uses a qualitative method with a psychological approach, employing David Krech's theory. The film tells the story of bullying during the coronavirus pandemic. This study uses documentation techniques from scenes and dialogues in the film. The findings from the analysis of the film Budi Pekerti reveal several key data points: the psychological dynamics experienced by Mrs. Prani, her various efforts to address the issues, and the internal and external factors influencing her behaviour. The study identified external factors but did not find any internal factors. Additionally, the roles of emotions, motivation, and perception in shaping Mrs. Prani's character were examined. In terms of emotions, Mrs. Prani defends herself by answering questions from other teachers and family members with controlled emotions. In terms of motivation, Mrs. Prani always motivates her students to be better. In terms of perception, there are many perceptions from family, teachers, students, and the surrounding community that cause Mrs. Prani to be cornered and always blamed.